PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI - rahmah kamilah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the difficulty of students in writing descriptive text. Students are less confident in pouring ideas more and dare to describe them through writing. This greatly affects the low student learning outcomes. Researchers used quantitative descriptive methods, namely methods with the aim of describing, explaining, and analyzing the problems contained in a study. The formulation of the problem in this study is whether the jigsaw type of cooperative learning method can influence the learning outcomes of class VII MTs students in writing descriptive texts. The purpose of this study was to determine the effectiveness of the type of jigsaw cooperative learning method for the effect of student learning outcomes in making descriptive texts. Class VII D students of TMI AL-BASYARIYAH 2 Bandung, totaling 43 people. The instrument used in this study was to test performance. The data of this research is the score of writing the results of the descriptive writing skills using the jigsaw cooperative learning model. The data were collected through a job test showing the structure of the description text. The average count of the descriptive text writing skills is 90.62, the diction elements of the description text are 76.56, the contents of the description text. The average count of descriptive text writing skills was 81.77. The use of the type of jigsaw cooperative learning affects the writing skills of descriptive texts for students, as evidenced by the results of the calculation of increasing descriptive text writing skills.